Contribution of Functional LILRA3, but Not Nonfunctional LILRA3, to Sex Bias in Susceptibility and Severity of Anti–Citrullinated Protein Antibody–Positive Rheumatoid Arthritis. Issue 4 (April 2014) - Du, Yan; Cui, Yong; Liu, Xia; Hu, Fanlei; Yang, Yue; Wu, Xinyu; Liu, Xu; Ma, Xiaoxu; Zuo, Xianbo; Sheng, Yujun; Liu, Xiangyuan; Xu, Jianhua; et al.
<x xml:space="preserve">Abstract</x> Objective Leukocyte immunoglobulin‐like receptor A3 belongs to a family of receptors with inhibitory or activating functions. Since Caucasian individuals lacking LILRA3 have been found to be susceptible to multiple sclerosis and Sjögren's syndrome, we undertook this study to examine whether LILRA3 deletion is a novel genetic risk factor for rheumatoid arthritis (RA) (another autoimmune disease), whether there are sex‐specific effects, and whether LILRA3 influences the subtype and severity of RA. Methods The LILRA3 deletion and its tagging single‐nucleotide polymorphism rs103294 were genotyped in a Northern Han Chinese cohort (N‐Han) (1, 618 cases and 1, 658 controls) and a Southern Han Chinese cohort (S‐Han) (575 cases and 549 controls). Association analyses were performed on the complete data set and subsets. The effect of the nondeleted (functional) LILRA3 allele on radiographic severity and LILRA3 expression was evaluated. Results In the N‐Han discovery cohort, we unexpectedly observed a higher frequency of the functional LILRA3 in RA patients compared with healthy individuals (10.1% versus 6.3%; P = 4.01 × 10−5, odds ratio [OR] 1.92). The association was replicated in the S‐Han cohort and confirmed by meta‐analysis (P = 5.63 × 10−6, OR 1.83). Functional LILRA3 conferred greater risk for RA in males (P = 1.09 × 10−6, OR 4.47), and was specifically associated with anti–citrullinated protein antibody (ACPA)–positive RA (P = 3.05 × 10−4, OR 1.75). Furthermore, functional LILRA3 was associated with higher radiographic scores in ACPA‐positive patients with early RA (P = 9.70 × 10−3) and higher LILRA3 messenger RNA levels (P = 3.31 × 10−8). Conclusion Our study provides the first evidence that functional LILRA3 is a novel genetic risk factor for RA, especially in males. It appears to highly predispose to ACPA‐positive RA and confers an increased risk of disease severity in patients with early RA.